2001
DOI: 10.1007/s001090100255
|View full text |Cite
|
Sign up to set email alerts
|

Sibling-based association study of the PPARγ2 Pro12Ala polymorphism and metabolic variables in Chinese and Japanese hypertension families: a SAPPHIRe study

Abstract: The peroxisome proliferator activated receptor (PPAR) gamma2 is a transcription factor that has been shown to be involved in adipocyte differentiation, adipogenesis, and insulin sensitivity. To address the role of PPARgamma2 in glucose homeostasis and insulin sensitivity, among many other objectives, we conducted a sibling-controlled association study in a multicenter program - the Stanford Asian-Pacific Program in Hypertension and Insulin Resistance (SAPPHIRe). Approximately 2525 subjects in 734 Chinese and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 31 publications
2
42
0
Order By: Relevance
“…A power calculation based on these data revealed a required sample size of ϳ2,000 to achieve significance. In a Chinese/Japanese sib-pair study, which by design controlled relatively well for genetic background and childhood environment, a greater estimated insulin sensitivity (homeostasis model analysis) was observed in carriers of the Ala allele (28). Interestingly, a more pronounced effect of the Pro12Ala polymorphism on insulin sensitivity was observed before the background of the common Gly972Arg polymorphism in insulin receptor substrate-1 (29).…”
Section: Effect On Insulin Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…A power calculation based on these data revealed a required sample size of ϳ2,000 to achieve significance. In a Chinese/Japanese sib-pair study, which by design controlled relatively well for genetic background and childhood environment, a greater estimated insulin sensitivity (homeostasis model analysis) was observed in carriers of the Ala allele (28). Interestingly, a more pronounced effect of the Pro12Ala polymorphism on insulin sensitivity was observed before the background of the common Gly972Arg polymorphism in insulin receptor substrate-1 (29).…”
Section: Effect On Insulin Sensitivitymentioning
confidence: 99%
“…Cross-sectional studies with small to moderate sample sizes yielded inconsistent results by demonstrating either no difference (21,23,28,38,39) or a modestly greater BMI in carriers of the Ala allele (10,40,41). Two sufficiently large studies (Ͼ1,000 nondiabetic subjects) found a lower BMI in Finns (11) and no difference in Japanese (15).…”
Section: Effect On Obesitymentioning
confidence: 99%
“…Previously we reported the association of the PPARγ 2 Ala12 variant with betType 2 diabetes mellitus (T2DM) has daunted many countries in the developed or developing world [1]. Insensitivity to insulin stimulation is generally accepted ter glucose tolerance and insulin sensitivity among subjects from Japanese and Chinese hypertension families in the Stanford Asia Pacific Program in Hypertension and Insulin Resistance (Sapphire) study [9]. Due to its family-based study design utilizing the comparisons between siblings, the genetic association study in Sapphire was expected to have better control in early childhood environmental factors and genetic background than a population-based genetic association study [9,10,11].…”
mentioning
confidence: 99%
“…Therefore, it is reasonable to believe that mortality in the nonagenarian/centenarian Adjusted multiple logistic regression was used to adjust for covariates OR odds ratio, Unadjusted Wald Chi-square test with df=1 was used, Model 1 adjustment made with covariates which might be associated with cognitive function at baseline (P<0.05 shown in Table 1), Model 2 adjustment made with covariates which might be associated with Pro12Ala (P<0.05 shown in Table 2), Model 3 adjustment made with all the covariates group may alter the association between dementia and Pro12Ala Polymorphism in PPAR-γ2. In addition, the prevalence of Ala12 allele varied greatly in different ethnic populations, with the prevalence rate being much lower in Asians than in Caucasians (Chuang et al 2001;Tai et al 2004). Therefore, ethnicity might also be an influencing factor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prevalence of Ala12 allele varied greatly among different ethnic populations, with the prevalence being much lower in Asians than in Caucasians (Chuang et al 2001;Tai et al 2004). The relationship between Pro12Ala polymorphism in PPAR-γ2 and dementia in the very-elderly population might be different from that in old people aged 60 years and above, and the allele frequency of Ala12 in PPAR-γ2 varies greatly in different ethnic populations.…”
Section: Introductionmentioning
confidence: 98%